A revisit to the [Num-Cl-Modifier- de -N]/ [Modifier- de -Num-Cl‑N] variation in Mandarin Chinese - Jin, Jing (Language and linguistics (Taipei), 2020)
This paper investigates the licensing condition of the [Num(eral)-Cl(assifier)-Mod(ifier)- de -N(oun)] / [Mod- de -Num-Cl‑N] variation in Mandarin Chinese. It is observed that this variation represents a complex interface phenomenon in the nominal domain, which is subject to the semantic condition concerning the i(ndividual)-level/​s(tage)-level nature of the modifier contained on the one hand, and the discourse-related condition concerning contrastive topic ( ct ) on the other. Based on this, at the syntax-semantics interface level, this paper proposes a division of the syntactic domain of adnominal modification to account for the discrepancy between i‑level and s‑level modifiers in terms of their capability in forming [Mod- de -Num-Cl‑N] in the neutral context. In the meanwhile, at the syntax-discourse interface level, in light of the interface-induced analysis pursued by Neeleman & Van de Koot (2008) and Horvath (2010) , it is claimed that the word order of [Mod- de -Num-Cl‑N] could be adopted as a linguistic device to encode ct within the nominal domain in Mandarin Chinese, in which case the ordering of [Mod- de -Num-Cl‑N] is licensed for the purpose of establishing a transparent mapping between syntactic configuration and information structure.